Level of competitive success achieved by elite athletes and multi-joint proprioceptive ability. Issue 1 (January 2015) - Han, Jia; Waddington, Gordon; Anson, Judith; Adams, Roger
Abstract Objectives Proprioceptive ability has been suggested to underpin elite sports performance. Accordingly, this study examined the relationship between an athlete's proprioceptive ability, competition level achieved, and years of sport-specific training. Design Cross-sectional study. Methods One hundred elite athletes, at competition levels ranging from regional to international, in aerobic gymnastics, swimming, sports dancing, badminton and soccer, were assessed for proprioceptive acuity at the ankle, knee, spine, shoulder, and finger joints. An active movement extent discrimination test was conducted at each joint, to measure ability to discriminate small differences in movements made to physical stops. Results Multiple regression analysis showed that 30% of the variance in the sport competition level an athlete achieved could be accounted for by an equation that included: ankle movement discrimination score, years of sport-specific training, and shoulder and spinal movement discrimination scores (p < 0.001). Mean proprioceptive acuity score over these three predictor joints was significantly correlated with sport competition level achieved (r = 0.48, p < 0.001), highlighting the importance of proprioceptive ability in underpinning elite sports performance. Years of sport-specific training correlated with an athlete's sport competition level achieved (r = 0.29, p = 0.004), however, proprioceptive acuity was not correlated with years of sport-specific training, whether averaged over joints or considered singly for each joint tested (all r ≤ 0.13, p ≥ 0.217). Conclusions Proprioceptive acuity is significantly associated with the performance level achieved by sports elites. The amount of improvement in proprioceptive acuity associated with sport-specific training may be constrained by biologically determined factors.